Feminizm amerykański trzeciej fali – zmiana i kontynuacja - Strand, Grażyna (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2011)
The history of American women fighting for equal rights dates back to the 18th century, when in Boston, in 1770, they voiced the demand that the status of women be changed. Abigail Adams, Sarah Grimke, Angelina Grimke and Frances Wright are considered to have pioneered American feminism. An organized suffrage movement is assumed to have originated at the convention Elizabeth Stanton organized in Seneca Falls in 1848. This convention passed a Declaration of Sentiments, which criticized the American Declaration of Independence as it excluded women. The most prominent success achieved in this period was the US Congress passing the Nineteenth Amendment to the Constitution granting women the right to vote. The 1960s saw the second wave of feminism, resulting from disappointment with the hitherto promotion of equality. The second-wave feminists claimed that the legal reforms did not provide women with the changes they expected. As feminists voiced the need to feminize the world, they struggled for social customs to change and gender stereotypes to be abandoned. They criticized the patriarchal model of American society, blaming this model for reducing the social role of women to that of a mother, wife and housewife. They pointed to patriarchal ideology, rather than nature, as the source of the inequality of sexes. The leading representatives of the second wave of feminism were Betty Friedan (who founded the National Organization for Women), Kate Millet (who wrote Sexual Politics), and Shulamith Firestone (the author of The Dialectic of Sex: The Case for Feminist Revolution). The 1990s came to be called the third wave of feminism, characterized by multiple cultures, ethnic identities, races and religions, thereby becoming a heterogenic movement. The third-wave feminists, Rebecca Walker and Bell Hooks, represented groups of women who had formerly been denied the right to join the movement, for example due to racial discrimination. They believed that there was not one ‘common interest of all women’ but called for leaving no group out in the fight for the equality of women’s rights. They asked that the process of women’s emancipation that began with the first wave embrace and approve of the diversity of the multiethnic American society.
American Feminism – the Third Wave. The Change and Continuation